Nature of Industry and Auditor Changes Influencing Fraudulent Financial Statements: Financial Stability as a Moderator - Dhini Suryandari; Indira Januarti (Universitas Negeri Semarang, 2025)
Purposes: This study examines the relationship between the nature of industry and auditor changes on fraudulent financial statements. In addition, this study uses financial stability as a moderating variable in the relationship between the nature of industry, auditor changes, and fraudulent financial statements.Methods: This study uses technology sector companies listed on the Indonesia Stock Exchange (IDX) from 2020-2023, with a total analysis unit of 111. This study uses Moderated Regression Analysis (MRA) with Eviews.Findings: The study's results indicate that the nature of industry and auditor changes positively affect fraudulent financial statements. In addition, financial stability moderates the relationship between the nature of the industry and fraudulent financial statements. However, financial stability cannot moderate the relationship between audit changes and fraudulent financial statements.Novelty: To the best of the researcher's knowledge, this is the first research that uses financial stability as a moderator in the framework of the relationship between the nature of industry and auditor changes on fraudulent financial statements